2003
DOI: 10.1038/sj.bmt.1704234
|View full text |Cite
|
Sign up to set email alerts
|

Gastric emptying after autologous haemopoietic stem-cell transplantation: a prospective trial

Abstract: Summary:Gastroparesis may be involved in the pathophysiology of prolonged nausea and vomiting after haemopoietic stemcell transplantation (HSCT), but this has not been prospectively investigated. Gastric emptying (GE) was investigated in 20 patients before and 2 months after autologous HSCT. Gastrointestinal symptoms were graded prospectively and oral energy intake was recorded in parallel. Before transplant, all patients were asymptomatic and GE was within the reference range. Post transplant GE was delayed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…One of the limitations of EN was vomiting, possibly related to the toxicity of conditioning and/or gastroparesis after SCT (23,24). The following moves improved tolerance to EN: 1) deferral of feeding tube insertion until the end of conditioningVideally the day after transplantation but before the onset of mucositisVleading to satisfactory tolerance of the device; 2) use of an NGT rather than a nasojejunal tube because of its ease of installation; and 3) a gradual increase in the infused volume, which may have overcome the gastroparesis effect (16,20).…”
Section: Discussionmentioning
confidence: 99%
“…One of the limitations of EN was vomiting, possibly related to the toxicity of conditioning and/or gastroparesis after SCT (23,24). The following moves improved tolerance to EN: 1) deferral of feeding tube insertion until the end of conditioningVideally the day after transplantation but before the onset of mucositisVleading to satisfactory tolerance of the device; 2) use of an NGT rather than a nasojejunal tube because of its ease of installation; and 3) a gradual increase in the infused volume, which may have overcome the gastroparesis effect (16,20).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in duodenal epithelium have persisted as long as 12 weeks after transplantation. 23 In addition, gastroparesis may be covert in adults receiving HSCT, 24 or the symptoms may be subtle and dismissed or misunderstood. Therefore, gut and pancreatic function may substantially influence cyclosporine absorption and bioavailability and dramatically change over time as these processes improve or worsen.…”
Section: Discussionmentioning
confidence: 99%
“…34 Gastroparesis of uncertain etiology may be a primary cause of nausea in BMT. 35 Eagle et al 36 evaluated 151 transplant patients during a 1-year period and found that gastroparesis was a significant cause of persistent nausea in 12% of patients. Factors such as age, conditioning regimen, CMV antigenemia and acute GVHD were not significant; however, receiving allogeneic transplantation was a significant factor.…”
Section: Nausea and Vomitingmentioning
confidence: 99%